Serial optical frequency domain imaging in STEMI patients: the follow-up report of TROFI study. (1st September 2014) - García-García, Hector M.; Muramatsu, Takashi; Nakatani, Shimpei; Lee, Il Soo; Holm, Niels Ramsing; Thuesen, Leif; van Geuns, Robert-Jan; van der Ent, Martin; Borovicanin, Vladimir; Paunovic, Dragica; Onuma, Yoshinobu; Serruys, Patrick W.
Abstract: Aims: To investigate the incidence of incomplete stent apposition and to explore the impact of the presence of thrombus and protruding plaque after stent implantation on neointima formation at follow-up in ST-segment elevation myocardial infarction (STEMI) patients with serial optical frequency domain imaging (OFDI) investigations. Methods and results: In a multi-centre study, 141 patients with ST elevation myocardial infarction <12 h from onset were randomized to either PPCI with thrombectomy (TB) using an Eliminate catheter (TB: n = 71) or without TB (non-TB: n = 70). OFDI after drug-eluting stenting was performed using TERUMO OFDI system. Per protocol, at follow-up 49 patients segments were reimaged. At post-procedure and follow-up, there were no differences in stent and lumen areas between the two groups. At follow-up, per strut-level analysis, percentage of incompletely apposed struts was 0.42 ± 0.94 vs. 0.38 ± 0.77% ( P = 0.76), and percentage of covered struts was 92.7 ± 7.2 vs. 94.4 ± 9.2% ( P = 0.47) in the TB and non-TB groups, respectively. There was a positive correlation between intra-stent structure (ISS) volume at post-procedure and the neointima volume at 6-month follow-up (Pearson's r = 0.409, P = 0.04). Up to 12 months, there have been two and four patients having target vessel failure in the TB and in the non-TB groups, respectively. Conclusions: In patients with STEMI, there were no significant differences in OFDI parameters between TB and non-TB groups at both post-procedure and 6-month follow-up. However, ISS volume at post-procedure was positively associated with neointimal volume at 6-month follow-up.